EFFECT OF DYNAMIC LOADS ON THE COMPRESSIBILITY OF PEAT SOIL REINFORCED BY BAMBOO GRIDS - Waruwu, Aazokhi; Susanti, Rika Deni; Buulolo, Johan Adolf Putra (Journal of Applied Engineering Science, 2019)
The compression behavior of peat was investigated by a program of static and dynamic load testing. The comprehensive model tests were conducted in the laboratory to evaluate the effect of loading sequences on the behavior of peat soil. The result test indicated that compression behavior of peat soil was significantly influenced by loading sequences and reinforcement of bamboo grids. The compression behavior after the dynamic load appears smaller than before the dynamic load. Reinforcement of bamboo grids can reduce the compressibility of peat soil, especially for one layer and two layers of bamboo grid, while for three layers of bamboo grid resulted in similar settlement for two layers of bamboo grid on the pressure above 9 kPa.